Adsorption of lead (II) ions in charcoal made from coconut (Cocos nucifera) shell - Firmalino-Javelosa, Karen Ann
Charcoal prepared from coconut shell (Cocos nucifera) locally acquired from the market of Jaro, Iloilo City was used for the removal of Pb(II) ions from aqueous solutions. The effect of pH and initial concentration was studied through batch sorption experiments. Equilibrium data were analysed by the Langmuir and Freundlich isotherm models. Langmuir isotherm was found to provide the best fit model based on the equilibrium data with maximum adsorption capacity of 2.80 mg/g. The maximum removal of Pb(II) was observed at 30 ppm initial concentration with 97.63% removal by coconut shell charcoal at one hour contact time and 0.2 grams charcoal. FT-IR experiments revealed alkyl C-H stretches, residual carbon dioxide and an ester C=O stretch in the original coconut shell charcoal. FT-IR readings of charcoal adsorbed with Pb(II) revealed weakened alkyl C-H and ester C=O stretches and the appearance of weak C=C stretches.